DISCOURSE ON PROFESSIONALISATION IN THE PRACTICE OF PUBLIC HEALTH PROFESSIONALS PROVIDING SERVICES TO PERSONS WITH DISABILITIES - Anužienė, Birutė; Norkiene, Sigute; Varopjeva, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article is aimed to discuss findings of the study on professionalisation in the practice of public health professionals who provide services to persons of all ages with disabilities. The following problematic questions are raised: how does a public health specialist become a professional competent in providing their services to all citizens, regardless of age or health status? What are the possible professionalisation ways and opportunities for public health professionals who provide services to persons of different age with disabilities? The article presents a theoretical discourse of the professionalisation process, as well as results of the qualitative research so as to provide insight into possible ways (opportunities) for professionalisation of public health professionals in providing services to persons of different ages with disabilities. The study is novel in that it discloses dimensions (professionalism and professionism) of a public health specialist’s professionalisation process in working with persons of different ages with disabilities. As findings of the study show, the dimensions are theoretically inseparable from each other, though, with quite different ways of professionalisation in practice. The study has established that the ways of professionalisation (1.Work-based learning; 2.Reflection and activities; 3.Reflection on activities (formalisation of unexpressed competencies); 4.Reflection for activities; 5.Organisational culture and activities; 6.Integration/assimilation of knowledge) enable a person to develop existing competencies, to construct a professional identity through the integration of both aspects of relevance of professionalisation ways: practical activities and reflection.